Determination Of Biogenic Amines In Fish Based Products Using Liquid Chromatographic And Capillary Electrophoresis - Bakar, Padilah (2018)
Determination of biogenic amines (BA) in fish based products were carried out using two standard methods, reversed phase - high performance liquid chromato- graphy/UV-Vis (RP-HPLC/UV-Vis) and capillary electrophoresis with capacitively coupled contactless conductivity detection (CE-C4D). The objective of the study was to determine the level of BA in local fish based products for safety assurance using standardised method yet sensitive, simple and at low cost. Using RP-HPLC method, putrescine (PUT), cadaverine (CAD), histamine (HIS) and tyramine (TYR) were analysed in 15 local belacan products.